Morte e cultura fúnebre na Itabaianinha oitocentista : (1870-1880) - Santos, Ingara Carolinne da Siva (2022)
This work aimed to analyze the perspective of death through provincial and municipal discourses involved in the construction of the Senhor do Bomfim Cemetery in Villa de Itabaianinha (SE). Based on the perspective of Cultural History, the research is qualitative and quantitative, covering the period from 1870 to 1880, aiming to understand the different transformations in society through social representations and imaginaries around death, rituals and funeral practices. It was also tried to understand how public speeches were crucial for the construction of the cemetery: Senhor do Bomfim. The change of burial place from the church to the public cemetery generated debates within society, as hygienists, with their speeches around death, called for an end to burials in churches, since society was currently being infected by epidemic diseases, especially cholera. This caused the process of secularization of these spaces. The construction of the public cemetery gained a social representation in the face of death and the dead regarding the preservation of their memory within society. In this sense, the present research permeates the ways in which Itabaianinha‘s society dealt with the process of death and life and how the public discourses related to the effectiveness of the Senhor do Bomfim cemetery were constructed.